Peraturan Daerah Bernuansa Syari’ah Di Indramayu Dan Tasikmalaya: Agama, Politik Lokal Dan Ancaman Disintegrasi - Isroji Isroji; Agus Moh. Najib (Universitas Cokroaminoto Yogyakarta, 2022)
Regional regulations with sharia nuances in Indonesia reap pros and cons because Indonesia is not a religious state. Indramayu Regency and Tasikmalaya City are two regions that apply sharia-based regional regulations. This research belongs to the type of qualitative research, using descriptive analytical method with a normative-juridical approach and maqashid shari'ah. The promulgation of sharia regulations in Indramayu and Tasikmalaya City is due to electoral political interests because the majority of the population in these two districts/cities are devout Muslims and fanatic towards sharia. In terms of implementation, the Syari'ah regional regulations in the two regencies/cities still tend to be discriminatory because not all residents are Muslim. The existence of the Syari'ah Regional Regulation is not in accordance with Pancasila and the 1945 Constitution because it only favors one religion. Shari'ah regulations do not guarantee the benefit of humans as the goal of bringing down Islamic law to the earth (maqashid shari'ah).